Disgust Associated With Culture Mixing: Why and Who?. (November 2016) - Cheon, Bobby K.; Christopoulos, George I.; Hong, Ying-yi
Humans possess evolved mechanisms to detect and reject contamination by potentially harmful foreign substances. These mechanisms may also function in the rejection of violations in the social order. Here, we propose that the disgust evaluation system may also be sensitive to culture mixing, especially when elements of own and foreign cultures occupy the same space at the same time (culture fusion). Across four studies, we observe support for this prediction. Paralleling disgust ratings for contaminants mixing with pure objects associated with the self (Study 1A), representations of blending and fusion between elements of own and foreign cultures were rated as more disgusting than simultaneous presentation of the same cultural elements without fusion (Studies 1B and 2). Disgust toward culture fusion was observed over and above incongruity associated with mixing two in-group cultural representations (Study 4). Moreover, selective disgust toward in-group–out-group culture fusion was especially pronounced among those endorsing higher levels of patriotism (Studies 1B, 2, and 4), but not when culture fusion involved two foreign representations (Study 3). These findings support the notion that the architecture for pathogenic- and food-based disgust may have been extended to reject external threats to the fidelity of in-group identity markers by out-group influences.